Impact of Climate Change on Health and Well-Being of People in Hindu Kush Himalayan Region: A Narrative Review - Dhimal, Meghnath; Bhandari, Dinesh; Dhimal, Mandira Lamichhane; Kafle, Naviya; Pyakurel, Prajjwal; Mahotra, Narayan; Akhtar, Saeed; Ismail, Tariq; Dhiman, Ramesh C.; Groneberg, David A.; Shrestha, Uttam Babu; Müller, Ruth (Frontiers in Physiology, 2021)
Climate change and climatic variability affect everyone and every region of the world but the effects are nowhere more prominent than in mountain regions and people living therein. The Hindu Kush Himalayan (HKH) region is one of the largest mountain areas in the world that extends over more than 4.3 million km2 areas of eight countries: Nepal, Bhutan, Afghanistan, Bangladesh, China, India, Myanmar, and Pakistan and comprises approximately 18% of the world’s mountain areas. Climate change particularly changes in historic temperature and precipitation patterns and increased frequency and intensity of some extreme events are reported in the HKH region. The HKH region is warming at a rate higher than the global average and precipitation has also increased significantly over the last six decades. Historic and future changes in temperature and precipitation are expected to affect the climate-dependent sectors such as hydrology, agriculture, biodiversity and human health. This paper aims to document how climate change has impacted and will impact, health and wellbeing of the people in HKH region and offer adaptation and mitigation measures to reduce the impacts of climate change on health and wellbeing of the people in the region. The impacts of climate change are prominent on infectious diseases, non-communicable diseases, malnutrition and injuries in the region. Hence, climate change adaptation and mitigation measures are needed urgently to safeguard vulnerable population residing in the region.